The effectiveness of the Sarawak forest ordinance 1958 / Christina Supang Akal Umong…[et al.] - Akal Umong, Christina Supang; Charles Anthony, Ivy Stephanie; Bujang @ Sawal, Nur Rayyan; Alau Apui, Stephanie; Guuk, Veronica (2010)
This chapter is to explain the prouiems surrounuing tte Sarawak forest ordinance 1958. To this end, the chapter will explain the scenario behind the Ordinance. The purpose and objective of this research encompasses the examination of the effectiveness of the Ordinance, to highlight the effects of deforestation due to the Ordinance's effectiveness and to recommend better and more efficient law to the relevant authority. This research will be conducted by virtue of extensive library research as well as through comparison of laws in other countries. This study covers only Sarawak as the Sarawak Forest Ordinance 1958 will be the main law that will be extensively studied.